Rib fractures in professional baseball pitchers: mechanics, epidemiology, and management - Schowalter, S.; Le, B.; Creps, J.; McInnis, K. C. (Open Access Journal of Sports Medicine, 2022)
Pitching is a complex kinetic chain activity requiring the transfer of energy from the lower body, through the core and trunk, and finally through the arm to generate explosive acceleration of the baseball. As a result, large forces are generated in the trunk musculature and rib attachments from the late cocking phase of pitching through deceleration. The repetitive cumulative load and high pitch velocities put professional pitchers at risk of rib stress fracture. Given the potential for a prolonged recovery course and high rate of recurrence, early recognition of rib bone stress injury is critical to optimize care. Identifying torso strength imbalances, suboptimal pitching biomechanics (such as late or inadequate pelvic rotation), as well as metabolic deficiencies that may adversely affect bone health are essential to expedite safe return to play and prevent future injury. In this review, we discuss risk factors, mechanism of injury, typical clinical presentation, diagnostic imaging findings, and propose treatment and prevention strategies for rib stress fractures in overhand pitchers.